Investigation of effect on energy consumption of surface roughness in X-axis and spindle servo motors in slot milling operation - Ozturk, Burak; Ugur, Levent; Yıldız, Aytaç (Elsevier Sci Ltd, 2019)
The energy cost is a significant expense in the machining companies, and the reduction of energy consumption has a critical prescription in the industry. To increase energy efficiency, machine producers have contributed by developing advanced functions for machines. Besides these, one of the main purposes of machining is to bring the desired surface roughness to the best level. In this study, it is aimed to optimize cutting parameters to minimize the surface roughness and the energy consumption in the process of the 7075-aluminium material, which is commonly used in manufacturing industry, in CNC milling machine under dry cutting conditions. Therefore, a test list was created with Taguchi L9 experiment design the surface roughness and the power consumption of the machining centre were measured by processing in the CNC milling machine according to the tool diameter, cutting depth, cutting speed and feed rate parameters. The measured values were analyzed in the Minitab 17 program for the Taguchi method. According to the results of the analysis, X axis servo motor's P-cutting value is affected by the amount of depth of 82%. However, the spindle servo motor's P-cutting value was determined to be affected by the highest 34% cutting speed. The SEC (Specific Energy Consumption) value of both servo motors is affected by the maximum amount of depth. It is the amount of SCEC (Specific Cutting Energy Consumption) allows us to characterize machinability of the materials according to results from energy consumption. SCEC value is affected by the cutting speed 53% rate in the axis servo motor. In addition, it is affected by the feed rate of 43% in the spindle servo motor. (C) 2019 Elsevier Ltd. All rights reserved.
Keywords: Energy consumption; Taguchi method; Surface roughness; Cutting performance